Voting with feet: community choice in social dilemmas - Özgür Gürerk; Bernd Irlenbusch; Bettina Rockenbach (Institute for the Study of Labor (IZA), 2009)
Economic and social interactions often take place in open communities but the dynamics of the community choice process and its impact on cooperation of its members are yet not well understood. We experimentally investigate community choice in social dilemmas. Participants repeatedly choose between a community with and an alternative without punishment opportunities. Within each community a social dilemma game is played. While the community with punishment grows over time and fully cooperates, the alternative becomes depopulated. We analyze the success of this voting with feet mechanism and find that endogenous self-selection is key while slow growth is less decisive.
Keywords: C72; C92; H41; 330; Cooperation; social dilemmas; community choice; punishment; voting with feet; Abwanderung und Widerspruch; Kommunalpolitik; Gefangenendilemma; Trittbrettfahrerverhalten; Rechtsdurchsetzung; Binnenwanderung; Test; Public Choice